2018
DOI: 10.1093/humrep/dex385
|View full text |Cite
|
Sign up to set email alerts
|

Does the endometrial gene expression of fertile women vary within and between cycles?

Abstract: Funding was granted from the Tertiary Education Commission of New Zealand, Contract I.D.:UOOX06007. There are no competing interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…The endometrial biopsies from healthy participants were all taken at two time-points (ES and MS) within the same menstrual cycle. A recent study by Evans et al demonstrated that the prior collection of an LH + 2 sample does not affect the general gene expression level of a LH + 7 sample [50]. Their study data suggested that the expression of tested genes exhibited a stable pattern, which was not affected even when sampled twice in one cycle and is valid to predict endometrial receptivity in the subsequent cycles.…”
Section: Discussionmentioning
confidence: 99%
“…The endometrial biopsies from healthy participants were all taken at two time-points (ES and MS) within the same menstrual cycle. A recent study by Evans et al demonstrated that the prior collection of an LH + 2 sample does not affect the general gene expression level of a LH + 7 sample [50]. Their study data suggested that the expression of tested genes exhibited a stable pattern, which was not affected even when sampled twice in one cycle and is valid to predict endometrial receptivity in the subsequent cycles.…”
Section: Discussionmentioning
confidence: 99%
“…It must be acknowledged, however, that assessment of reproducibility is limited by the small numbers, the lack of abnormal mid-luteal test results, and use of a natural cycle. Interestingly, the concept of reproducibility of gene expression has been recently tested in six subjects with normal receptivity, comparing gene expression across multiple cycles using a whole-genome microarray (88), though the direct application of these data to the ERA remains uncertain.…”
Section: Endometrial Assessmentmentioning
confidence: 99%
“…Despite recent advances in assisted reproduction techniques (ART), implantation rates remain low after controlled ovarian stimulation (COS) for in vitro fertilization (IVF), and intracytoplasmic sperm injection (ICSI) treatments (van der Gaast et al, 2008). Embryonic implantation failure remains the major limitation of ART success (Evans et al, 2018;van der Gaast et al, 2008), and although embryo quality is the main determinant of implantation success, maturity and endometrial receptivity are important factors to consider. Embryo implantation followed by gestation depends on a viable and high quality embryo, a receptive endometrium and having a molecular "dialogue" between them (Dieamant et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research in this area has focused on finding a viable endometrial receptivity marker that may help to identify the best moment to perform an embryo transfer (Edgell et al, 2013;Evans et al, 2018;Kliman & Frankfurter, 2019;Miravet-Valenciano et al, 2015;Siristatidis et al, 2018). Histologically, endometrial maturity can be classified using the Noyes criteria (Kliman & Frankfurter, 2019;Noyes et al, 1950;Paulson, 2019), which characterizes the endometrium into its phases (Complementary table).…”
Section: Introductionmentioning
confidence: 99%